Photoelectrochemical sensing of bisphenol a based on graphitic carbon nitride/bismuth oxyiodine composites. Issue 13 (23rd January 2017) - Xu, Li; Yan, Pengcheng; Li, Henan; Ling, Siyan; Xia, Jiexiang; Xu, Qian; Qiu, Jingxia; Li, Huaming
Abstract : Graphitic carbon nitride/bismuth oxyiodine composites with excellent photoelectrochemical performance had been designed for sensitive PEC monitoring platform of bisphenol A. Abstract : Graphitic carbon nitride/bismuth oxyiodine (g-CN/BiOI) composites with excellent photoelectrochemical (PEC) performance have been designed for a facile and sensitive PEC monitoring platform of bisphenol A (BPA) for the first time. The g-CN/BiOI composites were synthesized by a facile microwave method with 1-butyl-3-methylimidazolium iodine ([Bmim]I) as precursor. The heterojunction comprising g-CN and BiOI has been fabricated. The internal electric field formed at the interface of the heterojunction contributed to the separation of photogenerated electron–hole pairs. Consequently, the g-CN/BiOI composites achieved a greatly improved photocurrent density (∼2-fold) compared to the pure BiOI. In addition, the photocurrent of g-CN/BiOI composites can be further enhanced by introducing BPA into the aqueous solution. The increased photocurrent was applied as the PEC detection signal to trace the concentration of BPA sensitively and effectively. The self-constructed BPA PEC sensor displayed a satisfactory sensing performance with a rapid response, a wide linear range (80–3200 ng mL −1 ) and a low detection limitation (26 ng mL −1, S/N = 3). Moreover, the BPA PEC sensor exhibited an agreeable anti-interference capacity and outstanding stability, and provided a promising analytical method to detect BPA in the environment.